2015
DOI: 10.14356/kona.2015009
|View full text |Cite
|
Sign up to set email alerts
|

Settling Suspensions Flow Modelling: A Review

Abstract: In spite of the widespread application of settling suspensions, their inherent complexity has yet to be properly predicted by a unified numerical model or empirical correlation, and usually industries still possess customized charts or data for their particular suspension. This is, clearly, rather inefficient and can lead to oversized dimensioning, low energy efficiency and even operation limitations/difficulties. In this manuscript a review of empirical correlations, charts and numerical models that have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…They considered three different particle sizes of 0.2, 0.7 and 1.4 mm for 0.5 to 5 m/sec velocity range and found that the irregularities goes up with particle's size due to gravitational effect. Silva et al [16] studied the settling behaviour of slurry flow and investigated the effects of flow velocity on it. Gopaliya and Kaushal [17] analysed the effects of grain sizes on the slurry flow characteristics in horizontal pipelines implementing RNG k-ɛ turbulence model.…”
Section: Introductionmentioning
confidence: 99%
“…They considered three different particle sizes of 0.2, 0.7 and 1.4 mm for 0.5 to 5 m/sec velocity range and found that the irregularities goes up with particle's size due to gravitational effect. Silva et al [16] studied the settling behaviour of slurry flow and investigated the effects of flow velocity on it. Gopaliya and Kaushal [17] analysed the effects of grain sizes on the slurry flow characteristics in horizontal pipelines implementing RNG k-ɛ turbulence model.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al [16] studied velocity effect and the settling characteristics of slurry flow. Gopaliya and Kaushal [17] studied the effect of particulate size on pressure drop and found that the pressure drop increases with increase in particulate size at all efflux concentration. Pani et al [18] studied the additives effect on the rheological behaviour of coal ash slurry.…”
Section: Introductionmentioning
confidence: 99%
“…When modeling fluid-particle flow in sealing problems, the model needs to be able to address not only fluid motion itself, but also the particle-fluid and the particleparticle interactions in an efficient fashion [11]. In this respect, the combination of computational fluid dynamics (CFD) and discrete element method (DEM) is recognized as one of the most powerful combinations for the numerical study of fluid-particle interactions, especially when a four-way coupling is paramount to obtaining simulation results that are realistic and accurate.…”
Section: Introductionmentioning
confidence: 99%